The Effect of Cooperative Learning Model Type of Team Assisted Indivisualization Assisted LKPD on Mathematics Learning Outcomes - Mentari Aulia Sari; Baharullah Baharullah; Rukli Rukli (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of the study was to determine the students' mathematics learning outcomes by using a cooperative learning model of team assisted individualization type assisted by hots-based worksheets; and the effect of cooperative learning model type team assisted individualization assisted LKPD based hots on students' mathematics learning outcomes. The method used is an experiment with sampling determined by taking the available classes without doing random sampling. The experimental class and control class were determined by lottery, the results of the draw determined that class V SD Mallengkeri I was the control class and class V was SD Mallengkeri II as the experimental class, namely the class that was given treatment. The data analysis technique in this study used descriptive statistical analysis. As a requirement, test requirements were carried out, namely normality test and homogeneity test using Kolmogorov-Smirnov and Levene's test. After that, the hypothesis is tested using the Paired sample test. The results showed that the mean of the experimental class was 81, 88 while the mean of the control class was 68, 88. Based on data analysis with the Paired sample test. which was carried out at the 95% confidence level, the results were 0.000 <0.05, which means H0 is rejected. To find out the difference in student learning outcomes and understanding between the experimental class and the control class, the N-gain test was carried out using the N-Gain formula. Based on the calculation results obtained, for the experimental class of 0.58 which shows an increase in understanding in the medium category. Based on these data, it can be concluded that the use of the Team Assisted Individualization learning model has an effect on the learning outcomes of fifth graders at SD Cluster III Tamalate Makassar